Legal Aspects Regarding Perpetrators of Sexual Deviance Involving Bondage, Dominance, Sadism, and Masochism in the City of Sorong - Saro Fitriani A. Rohma; Wahab Aznul Hidaya; Rajab Lestaluhu (Journal of Law Justice (JLJ), 2026)
This study aims to determine the legal aspects of perpetrators of BDSM violence, forms of protection for victims of BDSM violence, and the application of sanctions. The research method used is normative legal research supported by primary, secondary, and tertiary data. The novelty of this research shows that sadomasochism is categorized as a form of abuse in the context of sexual relations, because it is done intentionally to obtain sexual satisfaction by hurting one's partner. The results of this study show that the legal aspects of perpetrators of sexual deviance in the form of BDSM are, in fact, not specifically regulated, and there are no laws or regulations that permit such sexual deviance. Furthermore, legal protection for victims of BDSM violence must be provided, bearing in mind that everyone has the right to protection from violence and the right to be free from torture or treatment that degrades human dignity, as guaranteed in the 1945 Constitution of the Republic of Indonesia. The conclusion of this study shows that BDSM practices that contain elements of violence and cause physical and psychological suffering can be classified as abuse and/or sexual violence under Indonesian positive law. Sadomasochism, as a form of sexual deviance, is closely related to the increase in cases of sexual violence that are actually occurring in society. The provisions of Article 351 of the Criminal Code and the Child Protection Law and related regulations provide a strong legal basis for prosecuting perpetrators, regardless of whether they are married to the victim. The Sorong District Court Decision Number 118/Pen.Pid/2022/PN Son emphasizes that the practice of sexual deviance accompanied by coercion and violence, especially against children, is a serious criminal offense that must be processed and decided based on applicable law for the protection of victims and the enforcement of justice.